Волкот во фразеологијата: македонско – руски паралели - Мирчевска-Бошева, Биљана; Велjановска Катерина (SlavVaria, 2026)
The Wolf in Phraseology: Macedonian and Russian Parallels. This paper examines phraseological units containing the component wolf in Macedonian and Russian, with the aim of deepening the understanding of their semantic, cultural, and lexicographic dimensions. As a species embedded in the traditional human environment, the wolf has acquired a rich symbolic value, generating a network of associations that extend from notions of danger and ferocity to those of power, resilience, and survival. The analysis explores the correlation between dictionary definitions of the lexeme wolf in Macedonian and Russian lexicography and its realization within the phraseological systems of the two languages. Special attention is devoted to identifying the semantic dominants that structure the phraseological network of meanings, as well as to tracing the mechanisms by which these meanings are transmitted and transformed across linguistic and cultural contexts. The analyzed material has shown that the phraseological use of the lexeme wolf reflects the dynamic interaction between human experience, cultural stereotypes, and the perception of the animal world, forming a complex system of symbolic meaning. These units not only embody linguistic creativity but also function as a mirror of the cultural codes and worldview of the peoples who employ them.